(untitled) (Journal of Medical & Health Sciences Review, 2025)
Recently diabetes mellitus is ubiquitous and serious metabolic health issue globally. Various medications are attainable for their management but due to their significant adverse effect humankind are seeking traditional plants which are economical. Various herbs are employed for treatments have been used since thousands of years. The aim of current research is to review effect of easily available Pakistan plants in diabetic patients through questionaries. Total 5 easily available Pakistani medicinal plants including karela (Momordica charantia Linn), jamun (Syzygium cumini), ginger (Zingiber officinalis Roscoe), kalonji (Nigella sativa), neem (Azadirachta indica) described in this review. The effect of these Pakistani medicinal plants may hold up the diabetes complications and have a great value in diabetes treatment.